Social construction of law enforcement for sexual violence against women in Aceh Utara - Zulkifli, Zulkifli; Rahman, Arief; Martina, Martina; Mumtiza, Rizka; Risma, Mauliza (Universitas Negeri Yogyakarta, 2022)
The level and types of sexual violence crimes in Indonesia are increasing and worrying the public. Law enforcement efforts to overcome criminal acts of sexual violence are increasingly being implemented. This study aims to examine the social construction of law enforcement against the crime of sexual violence against women in Aceh Utara. Respondents in the study amounted to 21 people who were selected with accidental sampling. The types of data in the form of primary data and secondary data were analyzed descriptively qualitatively. The results of the study explain that the legal basis used in the law enforcement process of sexual violence against women in Aceh Utara is Aceh Qanun Number 6 of 2014 concerning Inayat Law. Criminal charges for perpetrators of sexual violence in Aceh are whipping, fines, and imprisonment. It was found that the criminal sanctions contained in the qanun jinayat were lighter than the national law. For this reason, it is necessary to revise the qanun to provide a more severe deterrent effect on perpetrators, protect witnesses and victims with adopting developments in national laws related to sexual violence while still referring to the Aceh's Islamic characteristics.